PENGARUH PENERAPAN ABSENSI FINGER PRINT TERHADAP DISIPLIN KERJA DINAS KOPERASI, USAHA MIKRO, PERDAGANGAN DAN PERINDUSTRIAN KABUPATEN TANAH BUMBU - Marya Yully C; Nadi Hernadi Moorcy (Jurnal GeoEkonomi, 2023)
The Effect of Applying Finger Print Absences on the Work Discipline of the Office of Cooperatives, Micro Enterprises, Trade and Industry in Tanah Bumbu Regency. The purpose of this study was to determine the effect of applying fingerprint attendance on the work discipline of the Cooperative, Micro Enterprise, Trade and Industry Office of Tanah Bumbu Regency. The method used is correlational research with a quantitative approach which aims to provide a fairly clear picture of the Effect of Finger Print Absence Application on the Work Discipline of the Office of Cooperatives, Micro Enterprises, Trade and Industry in Tanah Bumbu Regency. The study was conducted on 35 Covid-19 isolation nurses and was carried out for a month. The results showed that finger print attendance included comfort, safety and time effectiveness simultaneously had a significant effect on employee work discipline. and finger print attendance including comfort, safety and time effectiveness partially have a significant effect on employee work discipline and time effectiveness has a more dominant effect on employee work discipline.